Gasterosteus aculeatus F1 adult clutch size, average egg diameter, and maternal length depending on grandparent and parent heatwave treatment - Helen Spence-Jones; Lisa N S Shama (PANGAEA, 2025)
F1 adult clutch size (total eggs), average egg diameter (mm) plus the standard deviation, and maternal length (mm) depending on grandparent and parent heatwave treatment
In: Spence-Jones, H; Shama, LNS (2025): Stickleback (Gasterosteus aculeatus) marine heatwave experiment: F0 adult size and fecundity traits, F1 offspring growth, behavior and survival, and F2 offspring egg size, clutch size, and hatchling length [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973487